Conducting an In-depth Interview - Lisa A. Guion; David C. Diehl; Debra McDonald (EDIS)
In-depth interviewing is a tool for collecting rich information that can inform program development and evaluation. Learn the basics with this 3-page fact sheet written by Lisa A. Guion, David C. Diehl, and Debra McDonald, and published by the UF Department of Family Youth and Community Sciences, August 2011. (UF/IFAS photo by Marisol Amador)